Pengaruh Corporate Social Responsibility, Kualitas Audit, Dan Capital Intensity Terhadap Agresivitas Pajak Di Masa Pandemi - Prameswari, Salsabila; Budyastuti, Triyani (Gorontalo Accounting Journal, 2023)
This study aims to determine the impact of Corporate Social Responsibility, Audit Quality, and Capital Intensity on tax aggressiveness during pandemic. This study uses secondary data from annual financial reports of mining companies listed on the Indonesia Stock Exchange during 2018-2021. This type of research is quantitative research using purposive sampling as a sampling technique and obtained from 20 companies. The analytical method used is multiple regression analysisâ€”processing data using SPSS 22 for windows and Microsoft excel. The result of this research is that Corporate Social Responsibility has a significantly positive effect on Tax Aggressiveness,Â  Audit Quality has a significantly negative effect on Tax Aggressiveness, and Capital Intensity has a significantly negative effect on Tax Aggressiveness.